2006
DOI: 10.1002/esp.1414
|View full text |Cite
|
Sign up to set email alerts
|

The use of short‐lived radionuclides to quantify transitional bed material transport in a regulated river

Abstract: We investigate the use of the short-lived fallout radionuclide beryllium-7 ( 7 Be; t 1/2 = = = = = 53·4 days) as a tracer of medium and coarse sand (0·25-2 mm), which transitions between transport in suspension and as bed load, and evaluate the effects of impoundment on seasonal and spatial variations in bed sedimentation. We measure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Because of the time required to analyse each sample, it was not feasible to analyse replicate samples at each site or to analyse multiple samples from different locations in the reach. Previous work (Salant et al, 2006b) has demonstrated that variations in 7 Be/ 210 Pb across a channel are generally small (<10%) in these watershed and the variation in 7 Be activity from replicate samples at the same location much less.…”
Section: Fallout Radionuclidesmentioning
confidence: 69%
See 4 more Smart Citations
“…Because of the time required to analyse each sample, it was not feasible to analyse replicate samples at each site or to analyse multiple samples from different locations in the reach. Previous work (Salant et al, 2006b) has demonstrated that variations in 7 Be/ 210 Pb across a channel are generally small (<10%) in these watershed and the variation in 7 Be activity from replicate samples at the same location much less.…”
Section: Fallout Radionuclidesmentioning
confidence: 69%
“…More recently, Salant et al (2006b) . This collection schedule sought to capture the temporal changes in sediment radionuclide activity associated with varying seasonal flow regimes and short-term high discharge events.…”
Section: Fallout Radionuclidesmentioning
confidence: 99%
See 3 more Smart Citations